Nestle India Maggi : Rebuilding Trust - Taneja, Girish (Indian Journal of Marketing, 2017)
During the second half of 2015, Nestle India had to withdraw Maggi noodles from the Indian market as the Indian food regulator (FSSAI) banned it, considering it unsafe for consumption. The company refuted the claims of the food regulator and communicated it to the stakeholders through media. Nestle India approached Bombay High Court and got relief from the ban. During November 2015, Nestle India re-launched Maggi noodles in India. Now, the big question is that whether Nestle India timely responded to the crisis? Has Maggi been able to rebuild trust among consumers?